Detection of Aflatoxins and Proximate Analysis of Selected Different Processed Foods: Biscuits, Cakes and Noodles from Lahore, Pakistan: Detection of Aflatoxins in Foods (Biological Sciences - PJSIR, 2023)
The current study was conducted to assure quality of biscuits, cakes and noodles by determining aflatoxin B1 and proximate composition of the selected food products. A total of 60 samples (20 each of biscuits, cakes and noodles) were collected from diverse areas of Lahore. Aflatoxins were determined using thin layer chromatography by adopting standard method of the association of official analytical chemists (AOAC). The proximate composition was also determined for selective products. Different parameters like moisture, ash content, crude fiber, crude protein and crude fat in percentages were deter- mined in selected food products. The correlation of aflatoxins was calculated with each factor at significant level (P